First‐Principles Screening of 3d‐Transition‐Metal‐Doped Hydrous Cobalt Phosphate Catalysts for Enhanced Oxygen Evolution Reaction - Meena Rittiruam; Tinnakorn Saelee; Patcharaporn Khajondetchairit; Annop Ektarawong; Björn Alling; Rathawat Daengngern; Piyasan Praserthdam; Supareak Praserthdam (Advanced Theory and Simulations, 2025)
Abstract Hydrous cobalt phosphate (CoPO) is a promising OER catalyst, but its activity is limited by poor electron transport and weak intermediate binding. This study reveals how 3d transition metal dopants can be used to tune these properties through first‐principles calculations. Sc, Ti, V, and Cr improve catalytic activity by promoting electron transfer and stabilizing *O intermediates, while Mn, Fe, Cu, and Zn reduce performance. Among all candidates, Ni doping strikes the optimal balance, enhancing conductivity and providing moderate *O binding energy that minimizes overpotential. These trends follow electronic descriptors such as d‐band center and electronegativity, and are validated by volcano plot analysis. Ni‐CoPO emerges as the most effective design, offering a clear strategy for improving OER catalysts by controlling dopant identity and electronic structure.
Keywords: Electrocatalysts for Energy Conversion; Advanced battery technologies research; Electrochemical Analysis and Applications